Changes in endothelial function, arterial stiffness and blood pressure in pregnant women after consumption of high-flavanol and high-theobromine chocolate: a double blind randomized clinical trial. (3rd April 2018) - Babar, Asma; Bujold, Emmanuel; Leblanc, Vicky; Lavoie-Lebel, Élise; Paquette, Joalee; Bazinet, Laurent; Lemieux, Simone; Marc, Isabelle; Abdous, Belkacem; Dodin, Sylvie
ABSTRACT: Objectives : The aim of this 2-group, parallel, double blind single-centre RCT was to evaluate the acute and chronic impacts of high flavanol high theobromine (HFHT) chocolate consumption on endothelial function, arterial stiffness and blood pressure (BP) in women at risk of preeclampsia. Methods : 131 pregnant women considered at risk of preeclampsia based on uterine artery Doppler ultrasound were divided into two groups (HFHT or low flavanol and theobromine chocolate (LFLT). Acute changes in plasma flavanol and theobromine, peripheral arterial tonometry and BP were evaluated at randomization (0, 60 and 120 min after a single 40-g dose of chocolate) and again 6 and 12 weeks after daily 30-g chocolate intake. The EndoPAT 2000 provided reactive hyperemia index (RHI) and adjusted augmentation index (AIx) as markers for endothelial function and arterial stiffness, respectively. Results : Compared with LFLT, acute HFHT intake significantly increased plasma epicatechin and theobromine ( p  < 0.0001), decreased AIx ( p  < 0.0001) and increased diastolic BP (3.49 ± 3.40 mmHg increase in HFHT group vs 1.55 ± 2.59 mmHg increase in LFLT group, p  = 0.0008). Chronic HFHT compared with LFLT intake significantly increased plasma theobromine ( p  < 0.0001). No other significant within group or between group changes were observed. Conclusions : Acute consumption of HFHT, compared to LFLT, increased plasma epicatechin and theobromine concentrations and decreased arterial stiffness, with no effect on endothelial function and a marginal increase in diastolic BP. Chronic HFHT intake increased plasma theobromine, though it did not have positive impacts on endothelial function, arterial stiffness or BP when compared to LFLT in pregnant women at risk of PE.